Spontaneous Superficial Femoral Artery Mycotic Aneurysm - Kalpana Vijaykumar; Jia Sheng Tay; Tjun Yip Tang; Edward Tieng Chek Choke (Case Reports in Surgery)
Peripheral artery mycotic aneurysms are rare occurrences. In this case, we review a 52-year-old lady with poorly controlled diabetes who developed a spontaneous left superficial artery mycotic aneurysm. She underwent excision and subsequent extra-anatomic bypass with a great saphenous vein graft. She had full functional recovery after a short period of rehabilitation.